Characterization of active anticoagulant fraction and a fibrin(ogen)olytic serine protease from leaves of Clerodendrum colebrookianum, a traditional ethno-medicinal plant used to reduce hypertension. (28th October 2019) - Gogoi, Debananda; Ramani, Sheetal; Bhartari, Surbhi; Chattopadhyay, Pronobesh; Mukherjee, Ashis K.
Abstract: Ethnopharmacological relevance: Cardiovascular diseases are the major cause of mortality and morbidity, causing over 17.9 million deaths a year worldwide. Currently used therapy is often having side effects and expensive, dietary interventions and alternative medicines are required. Clerodendrum colebrookianum has been used to treat cardiac hypertension but anticoagulant potency was not evaluated. Aim of the study: To characterize an active anticoagulant fraction (AAFCC) and a 30 kDa fibrin(ogen)olytic serine protease (clerofibrase) isolated from aqueous leave extract of C. colebrookianum. Materials and methods: AAFCC/clerofibrase was subjected to extensive biochemical and pharmacological characterization including LC-MS/MS, amino acid compositional and GC-MS analyses. Interaction between clerofibrase with fibrinogen was studied by spectrofluorometric analysis. In vitro thrombolytic, antiplatelet and cytotoxicity assay were performed. In vivo toxicity, anticoagulant, defibrinogen and antithrombotic activities were determined on Swiss albino mice. Results: The in vitro anticoagulant activity of AAFCC was found to be superior to heparin and clerofibrase and comparable to Nattokinase and warfarin. The proteomics and amino acid composition analyses suggest that clerofibrase is a previously uncharacterized novel plant protease capable of degrading the -αβ chains of fibrinogen/fibrin. AAFCC/clerofibrase exerts their anticoagulant action via fibrinogenolytic activity and partially by antiplatelet activity albeit they have no effect on thrombin and FXa inhibition. The spectrofluorometric analysis revealed the binding of clerofibrase to fibrinogen but not to thrombin and FXa. The phytochemical constituents and bioactive components of AAFCC were characterized by biochemical, and GC-MS analyses. The AAFCC and clerofibrase inhibited collagen/ADP-induced mammalian platelet aggregation, showed in vitro thrombolytic activity, and non-cytotoxic to mammalian cells. The AAFCC showed and dose-dependent in vivo plasma defibrinogenating and anticoagulant activities and inhibited k-carrageen-induced thrombus formation in the tails of mice. Conclusion: The potent in vivo anticoagulant and antithrombotic effects of AAFCC suggests its pharmacological significance as herbal anticoagulant drug for the prevention and/or treatment of hyperfibrinogenemia- and thrombosis associated cardiovascular disorders. Graphical abstract: Image 1